CAUSES AND INCIDENCE RATE OF POSTPARTUM HEMORRHAGE AT KASSALA NEW HOSPITAL, SUDAN - Ali, Abdel Aziem A.; A. M MD, AbdAlla; Miskeen, Elhadi (Gezira Journal of Health Sciences; Vol 6 No 2 (2010), 2010)
Postpartum hemorrhage (PPH) is one of the top five causes of maternal mortality in both high income and low income countries, although the absolute risk of death is much lower in the former than the latter (1 in 100,000 versus 1 in 1000 births) (1) . The incidence of PPH varies widely, depending upon the criteria used to define the disorder. A reasonable estimate is 1 to 5 percent of deliveries (1,2) . The WHO estimate that obstetric hemorrhage complicates 10.55 of all live births in the world (13 795 000 women experiencing this problem in 2000) and 28% of all direct maternal deaths due to hemorrhage (132000 maternal deaths) (3) .